Loss of NSD2 causes dysregulation of synaptic genes and altered H3K36 dimethylation in mice - Kinoshita, Shiori; Kojima, Kazuaki; Ohnishi, Eriko; Takayama, Yuka; Kikuchi, Hiroki; Takada, Shuji; Nakabayashi, Kazuhiko; Kawai, Tomoko; Hata, Kenichiro (Frontiers in Genetics, 2024)
Background: Epigenetic disruptions have been implicated in neurodevelopmental disorders. NSD2 is associated with developmental delay/intellectual disability; however, its role in brain development and function remains unclear. Methods: We performed transcriptomic and epigenetic analyses using Nsd2 knockout mice to better understand the role of NSD2 in the brain. Results and Discussion: Transcriptomic analysis revealed that the loss of NSD2 caused dysregulation of genes related to synaptic transmission and formation. By analyzing changes in H3 lysine 36 dimethylation (H3K36me2), NSD2-mediated H3K36me2 mainly marked quiescent state regions and the redistribution of H3K36me2 occurred at transcribed genes and enhancers. By integrating transcriptomic and epigenetic data, we observed that H3K36me2 changes in a subset of dysregulated genes related to synaptic transmission and formation. These results suggest that NSD2 is involved in the regulation of genes important for neural function through H3K36me2. Our findings provide insights into the role of NSD2 and improve our understanding of epigenetic regulation in the brain.